THE ROLE OF WORK MOTIVATION IN MEDIATING EFFECT OF PROFESSIONALISM ON EMPLOYEE PERFORMANCE - Muhammad Fachmi; Zulkifli Sultan; Ali Murdhani Ngandoh (Universitas Muhammadiyah Kalimantan Timur, 2021)
This research was conducted to analyze the importance of professionalism in influencing civil servants' work motivation and performance in Makassar City. It also analyzes the role of work motivation as an intervening variable in seeing the effect of professionalism on employee performance. This research is a survey research using a quantitative research approach. In this study, Respondents were 80 employees who were civil servants in Makassar City, with the sampling technique using random sampling. Researchers used path analysis techniques with AMOS software and Sobel test to see the indirect effect in analyzing the data. The research results prove that the higher the professionalism, the higher the work motivation of civil servants in Makassar City, and the resulting performance will also increase. High work motivation can also improve employee performance. Furthermore, these findings also prove that work motivation plays an important role in mediating the effect of professionalism on civil servants' performance in Makassar City significantly.